LYPD3, a New Biomarker and Therapeutic Target for Acute Myelogenous Leukemia - Hu, Tingting; Zhang, Yingjie; Yang, Tianqing; He, Qingnan; Zhao, Mingyi (Frontiers in Genetics, 2022)
Background: Acute myelogenous leukemia(AML) is a nosohemia with the highest paediatric mortality rates and a relatively poor prognosis. C4.4A(LYPD3) is a tumorigenesis and high-glycosylated cell surface protein that has been proven to be linked with the carcinogenic effects in solid tumors, but no hematologic tumors have been reported. We focus on exploring the molecular mechanism of LYPD3 in the regulation of the occurrence and development of AML to provide a research basis for the screening of markers related to the treatment and prognosis. Methods: Datasets on RNA Sequencing (RNA-seq) and mRNA expression profifiles of 510 samples were obtained from Tcga-gtex on March 10, 2021, which included the information on 173 AML tumorous tissue samples and 337 normal blood samples. The differential expression, identification of prognostic genes based on COX regression model and LASSO regression were analyzed. And in order to better verify, experiments including gene knockdown mediated by SiRNA, cell proliferation assays and Western blot all were prefomed. we studied the possible associated pathways through which LYPD3 may have impact on the pathogenesis and prognosis of AML by GSEA. Results: A total of 11,490 differential expression genes (DEGs) were identified. Among them, 4,164 genes were upregulated, and 7,756 genes were downregulated. The univariate Cox regression analysis and LASSO regression analysis found that 28 genes including LYPD3, DNAJC8 and other genes were associated with Overall survial (OS). And after multivariate Cox analysis, a total of ten genes were considered significantly correlated with OS in AML including LYPD3, which had poor impact on AML(p <0.05). The experiment results also supported the above conclusion. We identifified 25 pathways including E2F signaling pathway, p53 signaling pathway, PI3K_AKT signaling pathway that were signifificantly upregulated in AML samples with high LYPD3 expression (p < 0.05) by GSEA. Further, the results of experiment suggested that LYPD3 participate in the development of AML through p53 signaling pathway or/and PI3K/AKT signaling pathway. Conclusion: This study first proved that the expression of LYPD3 was elevated in AML, which was correlated with poor clinical characteristics and prognosis. And LYPD3 participate in the development of AML through p53 or/and PI3K/AKT signaling pathway.